2014
DOI: 10.1242/dev.109421
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hair cell regeneration in the neonatal mouse cochlea in vivo

Abstract: There was an error published in Development 141, 816-829.Edwin W. Rubel was omitted from the authorship of the paper. The correct author list and affiliations appears above.In addition the Acknowledgements and Author contributions sections should read as follows. AcknowledgementsWe thank L. Tong and R. Palmiter (University of Washington) for Pou4f3DTR/+ mice and discussion; S. Baker (St. Jude) for Atoh1-CreERTM mice and discussion; R. Kageyama (Kyoto University) for Hes5-nlsLacZ mice; P. Chambon (Institut Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 0 publications
1
44
0
Order By: Relevance
“…However, an inability to recapitulate definitive HC regeneration in vivo (Lenoir et al, 1997; Parietti et al, 1998) cast doubt on the true regenerative potential of the neonatal rodent cochlea, and suggested that either culture conditions do not accurately recapitulate the native cochlear environment or that a method to damage HCs more acutely in vivo was required. Indeed, recent data from our lab and others suggest that, while constitutive proliferation of HCs and SCs has eluded detection beyond embryonic day (E)14.5 in the intact mouse cochlea, the expression of proliferating cell nuclear antigen (PCNA) persists postnatally (see Figure 1), new HCs continue to be added to the mouse cochlea when examined at postnatal day (P) 0 and P6 (Jan et al, Unpublished), and rapidly acute HC loss during the first postnatal week, in vivo , results in proliferation, differentiation, and a robust, if transient, regeneration of lost HCs (Cox et al, 2012a). Despite such promising findings, this first postnatal week appears to represent a critical window during which such endogenous regeneration and proliferation can occur (Cox et al, 2012a).…”
Section: Permanent Cell Cycle Exit During the Development Of Innermentioning
confidence: 99%
“…However, an inability to recapitulate definitive HC regeneration in vivo (Lenoir et al, 1997; Parietti et al, 1998) cast doubt on the true regenerative potential of the neonatal rodent cochlea, and suggested that either culture conditions do not accurately recapitulate the native cochlear environment or that a method to damage HCs more acutely in vivo was required. Indeed, recent data from our lab and others suggest that, while constitutive proliferation of HCs and SCs has eluded detection beyond embryonic day (E)14.5 in the intact mouse cochlea, the expression of proliferating cell nuclear antigen (PCNA) persists postnatally (see Figure 1), new HCs continue to be added to the mouse cochlea when examined at postnatal day (P) 0 and P6 (Jan et al, Unpublished), and rapidly acute HC loss during the first postnatal week, in vivo , results in proliferation, differentiation, and a robust, if transient, regeneration of lost HCs (Cox et al, 2012a). Despite such promising findings, this first postnatal week appears to represent a critical window during which such endogenous regeneration and proliferation can occur (Cox et al, 2012a).…”
Section: Permanent Cell Cycle Exit During the Development Of Innermentioning
confidence: 99%
“…In the recent years, there is growing concern about the HC regeneration and synaptic plasticity around the globe and the great achievements have been made in revealing the mechanism and strategies to recover hearing function in mammals [10, 13, 59, 101]. Different levels of HC regeneration could be achieved through the regulation of factors and signaling pathways, which play important roles during the development of mammalian inner ear [23, 34, 48, 59].…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of HC regeneration could be achieved through the regulation of factors and signaling pathways, which play important roles during the development of mammalian inner ear [23, 34, 48, 59]. Synapse and nerve fiber related markers are detected around the newly regenerated HCs [10, 34, 89]. However, we are still quite far from restoring the hearing function in the damaged inner ear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations